1998
DOI: 10.1103/physrevlett.80.778
|View full text |Cite
|
Sign up to set email alerts
|

Internal Dynamics and Elasticity of Fractal Colloidal Gels

Abstract: The dynamic structure factor of fractal colloidal gels is shown to exhibit a stretched exponential decay to a finite plateau with an exponent of about 0.7. The value of the plateau depends on both initial particle volume fraction f 0 and scattering wave vector. We show that this behavior results from the contribution of internal elastic modes of many length scales, and present a model which accounts for the data. From the observed plateau we determine that the very small elastic modulus scales as G ϳ f 3.9 0 ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

40
285
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(331 citation statements)
references
References 16 publications
(27 reference statements)
40
285
0
Order By: Relevance
“…4a illustrates, laponite suspensions following rejuvenation unexpectedly display a very similar increase in the plateau value despite the fact that the interparticle interactions are likely unaffected by the rejuvenation. One possibility for this increase in the rejuvenated laponite suspensions is a slow strengthening of force networks in the suspensions weakened by the shear flow and a concomitant decrease in thermal fluctuations of these networks that create a fast partial decay in g 2 (q, t) in analogy with the picture developed in [65]. Thus, the increase in the plateau value during formation and after rejuvenation could have different origins.…”
Section: Slow Dynamics and Aging In Some Jammed Systemsmentioning
confidence: 91%
See 1 more Smart Citation
“…4a illustrates, laponite suspensions following rejuvenation unexpectedly display a very similar increase in the plateau value despite the fact that the interparticle interactions are likely unaffected by the rejuvenation. One possibility for this increase in the rejuvenated laponite suspensions is a slow strengthening of force networks in the suspensions weakened by the shear flow and a concomitant decrease in thermal fluctuations of these networks that create a fast partial decay in g 2 (q, t) in analogy with the picture developed in [65]. Thus, the increase in the plateau value during formation and after rejuvenation could have different origins.…”
Section: Slow Dynamics and Aging In Some Jammed Systemsmentioning
confidence: 91%
“…In some cases, the characteristic relaxation time τ f measured for the faster, initial decay scales with q as τ f ∼ q −2 , indicating caged diffusive dynamics [2]. In the case of a fractal colloidal gel, the DSF f (q, t) characterising the initial decay exhibits a stretched exponential form with an exponent of 0.7 [65] and is understood in terms of the contribution of thermally excited, overdamped modes of the gel strands. The second, slower relaxation in these soft glassy materials is more counter-intuitive and is characterised by a DSF with a compressed exponential form (f (q, t) ∼ exp[−(t/τ s ) p ], where p ≈ 1.5), with τ s varying with q according to the relation τ s ∼ q −1 .…”
Section: Slow Dynamics and Aging In Some Jammed Systemsmentioning
confidence: 99%
“…It has inspired successful phenomenological gel models, e.g. [19,20,21], for which CMCT could provide a more rational (albeit still speculative) basis. Experiments [22] demonstrate that even for moderate attractions the assumed closeness to the ICA limit is well justified at low volume fractions in some cases, while in others the measured fractal dimension lies higher than for the appropriate ICA model [23].…”
Section: Pacs Numbersmentioning
confidence: 99%
“…Also Poon et al [11] have made such observations in the so-called transient gelation region of the colloid-polymer phase diagram for short polymers. Krall and Weitz [35] have shown that, in the limit of strong particle aggregation, suspensions become nonergodic even at low colloid densities. To date, however, only a speculative connection has been made between the gel and liquid-glass transitions [15].…”
Section: Introductionmentioning
confidence: 99%